Broad-spectrum synergistic antiviral activity of selenazofurin and ribavirin. - Kirsi, J J (1984)
The antiviral effects of selenazofurin (2-beta-D-ribofuranosylselenazole-4-carboxamide, selenazole), ribavirin (1-beta-D-ribofuranosyl-1,2,4-triazole-3-carboxamide), and 3-deazaguanosine (6-amino-1-beta-D-ribofuranosylimidazo-[4.5-C]pyridin-4(5H)-one) were investigated separately and in various combinations in an in vitro study. The combination interactions were evaluated at seven drug concentrations, graphically (isobolograms) or by using fractional inhibitory concentration indices against mumps, measles, parainfluenza virus type 3, vaccinia and herpes simplex virus type 2 viruses in Vero and HeLa cells. Selenazofurin in combination with ribavirin produced the greatest synergistic antiviral activity. However, the degree of synergy depended on the virus and cell line used. In contrast, selenazofurin combined with 3-deazaguanosine consistently yielded an indifferent or an antagonistic response, or both, whereas the ribavirin-3-deazaguanosine interaction was additive against the same viruses. Single-drug cytotoxicity was minimal for the cytostatic agents selenazofurin and ribavirin but was markedly higher for cytocidal 3-deazaguanosine, as determined by relative plating efficiency after drug exposure. The drug combinations did not significantly increase cytotoxicity (they were only additive) when used on uninfected cells. Therefore, the enhanced antiviral activities of the drug combinations (shown to be synergistic) were due to specific effects against viral replication. These results indicated that in Vero and HeLa cells (i) the combination of selenazofurin and ribavirin produced an enhanced antiviral effect, thus requiring smaller amounts of drug to cause the same antiviral effect relative to a single compound; (ii) selenazofurin when compared with ribavirin and 3-deazaguanosine appeared to have a somewhat different mode of antiviral action; (iii) 3-deazaguanosine combined with selenazofurin was an unsuitable antiviral combination; and (iv) the antiviral activity of 3-deazaguanosine appeared to be due largely to its general overall cytotoxic effect.